The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.18378/rvads.v10i5.3589
|View full text |Cite
|
Sign up to set email alerts
|

Análises físicas, composição centesimal e nutricional de minimilho (Zea mays, L.) orgânico de diferentes variedades

Abstract: Resumo: Atualmente os produtos orgânicos vêm roubando a cena dos produtos tradicionais, por serem saudáveis, livres de agrotóxicos e por gerarem menor impacto no meio ambiente. O minimilho (Zea mays, L.) também conhecido como "babycorn", uma espiga imatura ainda não fertilizada (espiguetas), é uma hortaliça, produto considerado fino que vem ganhando importância no mercado de conservas no Brasil. Esta pesquisa se propôs avaliar a qualidade de minimilho orgânico in natura de diferentes variedades e determinar a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
1
1
1
Order By: Relevance
“…15;2019Chitarra, 2005. The pH results obtained in this study agree with Lima et al (2015) that evaluated the quality of six varieties of organic baby corn, 'Pipoca', 'Super doce', 'Doce cristal', 'Eldorado', 'Cate-tinho' and 'Branco', confirming that the baby corn is an acid food, regardless of the studied varieties, without altering in great magnitude the level of acidity.…”
Section: Experiments Isupporting
confidence: 86%
See 2 more Smart Citations
“…15;2019Chitarra, 2005. The pH results obtained in this study agree with Lima et al (2015) that evaluated the quality of six varieties of organic baby corn, 'Pipoca', 'Super doce', 'Doce cristal', 'Eldorado', 'Cate-tinho' and 'Branco', confirming that the baby corn is an acid food, regardless of the studied varieties, without altering in great magnitude the level of acidity.…”
Section: Experiments Isupporting
confidence: 86%
“…B. Chitarra, 2005). Perfeito et al (2017), observed for sweet corn, soluble solids values ranging from 15.0 to 17.0 °Brix, while Lima et al (2015) working with baby corn, detected values ranging from 3.0 to 6.0 °Brix, and the results observed in the present study are lower than those found with sweetcorn and higher than the results obtained to baby corn by the authors (Table 1). In the evaluation of the SS/TA ratio, the samples stored at 25 °C without package were lower, evidencing a greater imbalance between the contents of sugars and acids of this vegetable (Table 1).…”
Section: Experiments Icontrasting
confidence: 71%
See 1 more Smart Citation
“…It does not happen when a higher starch level produces an undesirable dry or gritty texture [36]. Moisture is another very important parameter because it relates to the concentration of soluble components and it is associated with the physical fragility of the cultivar [37]. The values ranged from 61.12% (UENF 506-11) to 86.20% (UENF SD 08) (p ≤ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…O qual é a inflorescência feminina colhida após a emissão dos estilo-estigmas. Lima et al (2015) analisaram a composição de minimilho de seis variedades (Pipoca, Super Doce, Doce Cristal, Eldorado, Catetinho e Branco) produzidas em sistema orgânico em Seropédica/RJ; obtiveram valores de teores de umidade de 83,02 a 92,10%; cinzas de 0,32 a 0,70%; lipídeos de 0,83 a 1,14%; proteínas de 0,41 a 0,51% e carboidratos de 6,07 a 13,84%. As autoras concluíram que o minimilho tem a vantagem de ser uma hortaliça de baixo valor calórico.…”
Section: Introductionunclassified